2014
DOI: 10.1248/bpb.b14-00226
|View full text |Cite
|
Sign up to set email alerts
|

Δ<sup>9</sup>-Tetrahydrocannabinol Targeting Estrogen Receptor Signaling: The Possible Mechanism of Action Coupled with Endocrine Disruption

Abstract: Δ9 -Tetrahydrocannabinol (Δ 9 -THC), a biologically active constituent of marijuana, possesses a wide variety of pharmacological and toxicological effects (e.g., analgesia, hypotension, reduction of inflammation, and anti-cancer effects). Among Δ 9 -THC's biological activities, its recognized anti-estrogenic activity has been the subject of investigations. Since Δ 9 -THC is used as both a drug of abuse (marijuana) and as a preventive therapeutic to treat pain and nausea in cancer patients undergoing chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…17,23) We previously reported that Δ 9 -THC had the potential to abrogate E2/ERα signaling in MCF-7 cells by up-regulating ERβ, which resulted in the inhibition of cell proliferation, and also that Δ 9 -THC required the co-existence of ERα/ERβ to evoke its anti-proliferative effects. 17,29) Furthermore, Gustafsson and his colleagues showed that ERβ suppressed E2/ERα-mediated uterine progression in immature mice. 30) Although we observed the anti-estrogenic nature of BPAF in breast cancer cell lines (in vitro), BPAF may induce unwanted events via the perturbation of estrogen signaling after its accumulation in certain normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…17,23) We previously reported that Δ 9 -THC had the potential to abrogate E2/ERα signaling in MCF-7 cells by up-regulating ERβ, which resulted in the inhibition of cell proliferation, and also that Δ 9 -THC required the co-existence of ERα/ERβ to evoke its anti-proliferative effects. 17,29) Furthermore, Gustafsson and his colleagues showed that ERβ suppressed E2/ERα-mediated uterine progression in immature mice. 30) Although we observed the anti-estrogenic nature of BPAF in breast cancer cell lines (in vitro), BPAF may induce unwanted events via the perturbation of estrogen signaling after its accumulation in certain normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As we reported previously, the inhibitory efficacy of HU-210 on cell viability was more potent than that of ∆ 9 -THC (i.e., IC 50 = 34.5 μM) (Takeda et al, 2013). In this study, ∆ 9 -THC was utilized as a positive control in order to analyze the anti-estrogenic potential of HU-210 for E2/ ERα signaling (Takeda et al, 2013;Takeda, 2014). Based on their IC 50 values, we subsequently investigated the effects of the two cannabinoids on E2-driven ERα activation.…”
Section: Resultsmentioning
confidence: 82%
“…Martín-Calderón et al (1998) reported that HU-210 induced a set of endocrine alterations, such as plasma hormones including growth, luteinizing, and follicle-stimulating hormones, at doses 50 -200-fold lower than those required for ∆ 9 -THC in adult female rats. These effects of cannabinoids appear to be triggered by their activation of CB receptors; however, since the ∆ 9 -THC-mediated upregulation of ERβ was not negated by specific antagonists for CB1 and CB2 (Takeda, 2014), possible requirement(s) for the up-regulation of ERβ may not involve CB receptors. As clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations